Government Spending Shocks, Sovereign Risk and the Exchange Rate Regime - Dennis Bonam; Jasper Lukkezen (Tinbergen Institute, 2013)
Conventional wisdom teaches that the output response upon a fiscal expansion is higher under fixed than floating exchange rates for a small open economy. We analyse the effects of fiscal expansions using a New Keynesian model and find that this result reverses in times of sovereign default risk. Under a float, a fiscal expansion is followed by an exchange rate depreciation, which stimulates exports; under a peg, only the adverse effects of sovereign risk on private credit conditions and consumption remain. When these adverse effects are large, we show that a transient fiscal contraction may bring about positive output responses, yet only in the short run.
Keywords: E32; E52; E62; 330; Fiscal policy; government spending; exchange rate regime; sovereign risk; New Keynesian model; expansionary fiscal consolidation